Estudios genéticos de las incompatibilidades en los poliploides de brassica pekinensis rupr. (1961)
l. Todos los individuos de los 4 tipos de genotipos homocigóticos completos en cuanto al gene opuesto, indicaron autoincompatibilidad. 2. Todos los cruzamientos entre los individuos que tienen genotipos iguales los podemos considerar como cruzoincompatibles. 3. Todos los cruzamientos posibles de SaSaSaSa X SbSbSbSb, los cruzamientos recíprocos de SaSaSbSb X ScScScSc y los cruzamientos de SaSaSbSb X SaSaScSc y los cruzamientos de SaSaSbSb X ScScSdSd se pueden considerar como cruzocompatibles. 4. Los individuos de genotipo SaSaSbSb que son los híbridos F1 entre los individuos de genotipos homocigóticos completos, se pueden considerar como autoincompatibles. 5. En los cruzamientos de SaSaSaSa X SbSbSbSb, aún en el caso de que los pólenes SaSb y SbSb tengan las funciones activas en el estigma del individuo SaSaSaSa, la habilidad de fertilidad del pólen SaSb es más baja que la del pólen SbSb. 6. Los cruzamientos de SaSaSaSb X SaSaSaSa se pueden considerar comocruzoincompatibles. Al contrario, los cruzamientos de SaSaSaSb X SbSbSaSb y SaSaSaSb X ScScScSc se pueden considerar como cruzocompatibles. 7. Las fertilidades de semillas de los cruzamientos de SaSaSaSb X ScScScsc son más a altas que las de los cruzamientos de SaSaSaSb X SbSbSbSb. 8. Los cruzamientos de SaSbScSc X SaSaSaSa, SaSbScSc X SbSbSbSb y SaSbScSc X ScScScSc se pueden considera cama cruzoincompatibilidades. 9. Los cruzamientos de S1S2S3S4 X S1S1S1S1, S1S2S3S4 X S2S2S2S2, S1S2S3S4 X S3S3S3S3 y S1S2S3S4 X S4S4S4S4 indicaron cruzoincompatibilidades. 10. Todos los individuos con el genotipo de SaSaSaSb SaSaSbSc y SaSbScSd obtenidos hasta ahora indicaron autoincompatibilidades. 11. Relaciones de dominante a recesivo existen entre dos genes de los pólenes heteroalelicos respecto al gene opuesto en autotetraploides arificiales. Las relaciones fueron determinadas por el autor como sigue: S2 = Sa and gt;S4 and gt; S1 No obstante, consideramos que las relaciones de dominante a recesivo entre dos genes en los pólenes heteroalelicos respecto al gene opuesto, no son completas sino incompletas. 12. Estos fenómenos genéticos se explican con el sistema gametofítico en todos los casos. 13. Las relaciones directas respecto a la fertilidad de sus cápsulas fueron descritas entre los resultados de los cruzamientos recíprocos de 2x X 4x y de los genotipos opuestos de sus padres. No obstante, no fueron descritas respecto a la fertilidad de la semilla y la frecuencia de germinación de semilla F1. Pero, en las combinaciones compatibles de 2x X 4x fueron obtenidas muchas más semillas vanas y arrugadas que en los casos de combinaciones de los otros 3 tipos de cruzamientos recíprocos. Algunas consideraciones respecto a la función del gene opuesto en Brassicege han sido mencionadas por el autor./Abstract In the present paper, the behavior or the function of the oppositional genes in the artificial autotetraploids and the relationships between the results of the reciprocal crosses of 4x X 2x and their oppositional genotypes of Chinese cabbage (Brassica pekinensis Rupr.) were studied by the present author. In a diploid commercial variety “Kanazawa-Hakusai”, four homozygous strains, S1S1, S2S2, S3S3 and S4S4, were analysed by the ordinary cro-sing experiments, and their correspondent autotetraploids conducted by the dropping method of 0.2% aqueous solution of colchicines. 1. The results of the selfing, the primary and the secondary crosses were as follows: a) All the plants with SaSaSaSa type showed a self-and crosses incompatibility in the intra-group crossing among the individuals with the same genotype (Table 1). b) All the possible cross combinations with SaSaSaSa X SbSbSbSb type showed compatility (Table 2) c) The plants with SaSaSbSb type showed a self-and cross-incmpatibility in the intra-group crossing among the individuals with the same genotype (able 3 and amp; 4). d) In the cross combinations with SaSaSbSb X SaSaSa type, cross incompatibility were recognized. On the contrary, the reciprocal crosses showed cross compatibility (Table 5). e) The reciprocal crosses between SaSaSbSb and ScScScSc were always compatible (Table 6). f) The cross combinations with SaSaSbSb X SaSaScSc type and with SaSaSbSb X ScScSdSd type were always compatible (Table 7 and amp; 8). 2. Detailed gene analysis had been done in the offsprings of the next generation wich were obtained from 14 secondary cross combinations (Table 9 and amp; 10). As the results, the next facts were obtained: a) In the cross combination of SaSaSaSa X SbSbSbSb type, even if both SaSb pollen and SbSb pollen have jointly the germinative function on the style of SaSaSaSa plant, the ability of fertilization of SaSb pollen is more lower than that of SbSb pollen. b) The crosses with SaSaSaSb X SbSbSbSb type and with SaSaSaSb X ScScScSc type were compatibles. c) The ferlities of cross combinations with SaSaSaSb X ScScScSc type are higher than those of SaSaSaSb X SbSbSbSb type (Table 16 and amp; 17). d) The cross combinations with SaSaSbSc X SaSaSaSa type, SaSaSbSc X SbSbSbSb type and SaSaSbSc X ScScScSc type were incompatibles. e) The cross combinations with S1S2S3S4 X S1S1S1S1, S1S2S3S4 X S2S2S2S2, S1S2S3S4 X S3S3S3S3 and S1S2S3S4 X S4S4S4S4 type were incompatibles. f) All the plants with SaSaSaSb, SaSaSbSc and SaSbScSd type which were obtained until today showed self-incompatibility. g) In the diploid heteroallelic pollen grains with regard to the oppositional gene, S1 is recessive to all three of the other alleles, and S4 is the intermediate; S2 and S3 are dominant-recessive relationships are believed to be incomplete. 3. Those genetical phenomena are explained by the gametophytic system in all cases. 4. The relationships between the results of reciprocal crosses of 4x X 2x and their oppositional genotypes were as follows: a) There was clear diference between compatible and incompatible cross combinations with regard to the capacity of capsules set in the reciprocal crosses of 4x X 2x, on the contrary, there were no clear difences between both cross combinations with regard to seed fertility and germination capacity of F1 hybrids (Table 13 and amp; 14). b) The capsule setted on the compatible cross combination was more longer and wider than the capsule setted on the incompatible one in 4x X 2x, but there was no clear diference between both cross combinations in 2x X 4x. c) On the compatible cross combination in 2x X 4x, numerous empty and shriveled seeds were obtained than on the incompatible one. d) Seed fertilities on the compatible cross combinations in the reciprocal crosses of 4x X 2x were more lower than ones in the same cross combinations among 4x and 2x, respectively. 5. Some considerations with regard to the function of the oppositional gene in Brassiceae have benn done by the present author.